PSYCHOLOGICAL RESOURCES OF STRESS COPING SUBJECTS OF TEAM ACTIVITIES - Sovmiz, Z.R. (Modern Psychology, 2021)
This article discusses the features of inclusion of personality in individual and team coping. The study revealed the features of correlation of individual and team coping strategies of the subjects of team activities; individual and group coping resources; constraints to successful coping with stress; indirect inter-relation of individual resources with coping strategies group activity where the intermediary is group resources; specificity of athletic activities; reaction types of actors (group activity) on how they respond to stress. Obtained data allow to forecast the success rate of actors of team activity in the process of stress coping.
Keywords: subject of team activity; individual and group coping-strategies; individual and group coping-resources